Iliopsoas Muscle/Tendon Proportions at Three Levels of Described Arthroscopic Tenotomy: An Anatomic Study in Fresh Cadaveric Specimens (2020)
Purpose: To calculate the iliopsoas muscle/tendon ratio at 3 levels of arthroscopic iliopsoas tenotomy sites in fresh cadaveric specimens. Methods: An anatomic study design was performed using 16 iliopsoas musculotendinous units from the level of the hip joint to their insertion on the lesser trochanter. All specimens came from 16 fresh cadaveric specimens (10 male, 6 female), with a median age of 41 years (range 31-55.25 years). Circumferential measurements of the composite musculotendinous unit and the iliopsoas tendon were then made at the lesser trochanter insertion, the site of transcapsular tenotomy, and the site of tenotomy at the level of the labrum. Anatomical variance of the iliopsoas tendon at the insertion on the lesser trochanter and muscular extension below the lesser trochanter level also were described. The difference between the median circumference of the iliopsoas musculotendinous units or the isolated tendons at the 3 levels was calculated. Results: The median circumference of the iliopsoas musculotendinous unit at the level of the labrum, orbicularis zone (transcapsular tenotomy site), and the lesser trochanter was 140.9 mm (range 137.9-148.9), 136.7 mm (range 132.9-140), and 99.5 mm (range 96.5-104.8), respectively. The median circumference of the iliopsoas tendon at these same levels was 25.6 mm (range 22.7-33.7), 28.9 mm (range 25.1-32.2), and 30.9 mm (range 27.9-36.1), respectively. Accordingly, the proportions of the iliopsoas muscle/tendon at the level of the labrum, the transcapsular tenotomy site, and the lesser trochanter insertion were 18% tendon/82% muscle, 21% tendon/79% muscle, and 31% tendon/69% muscle, respectively. Conclusions: The proportions of the iliopsoas muscle/tendon at the level of the labrum, the transcapsular tenotomy site and the lesser trochanter insertion were 18% tendon/82% muscle, 21% tendon/ 79% muscle, and 31% tendon/69% muscle, respectively. The distal muscular projection below the tendinous insertion on the lesser trochanter may maintain the functional connection of the iliopsoas between origin and insertion even after releasing the tendon. Clinical relevance: This finding may have implications for a new understanding of arthroscopic tenotomy of the iliopsoas around the hip, as previously described muscle/tendon proportions were not calculated in fresh cadavers.